Integrated soil fertility management involving promiscuous dualpurpose soybean and upland NERICA enhanced rice productivity in the savannas - Oikeh, S.O.; Houngnandan, P.; Abaidoo, Robert C.; Rahimou, I.; Touré, A.; Niang, A.; Akintayo, I. (Springer, 2010)
Integrated soil fertility management (ISFM) involving a nitrogen-fixing grain legume, limited chemical fertilizer, and a resilient rice variety may reduce the rate of soil fertility loss and enhance rice productivity in fragile upland rice ecosystems. A 2-year, on-farm study was carried out at Eglimé in the southern Guinea savanna (SGS) and Ouake in the northern Guinea savanna (NGS) of the Republic of Benin to evaluate the contribution of dual-purpose soybean cultivars (Glycine max) to grain yield of upland NERICA® rice receiving low fertilizer N. In 2005, four dual-purpose, promiscuous soybean varieties (cv. TGX 1440-IE, TGX 1448-2E, TGX 1019-2EB, and TGX 1844-18E), a popular soybean variety (cv. Jupiter), and a popular rice (control) were sown in ten farmers’ fields. In 2006, resilient upland interspecific rice (NERICA1) and popular rice (IRAT-136) were sown in all plots with only 15 kg N ha−1. Soybean cv. TGX 1440-1E (late-maturing) ranked highest in nodulation, dry matter, shoot- and grain-N accumulation, and N-balance (21 kg ha−1) in NGS, while TGX 1448-2E (medium-maturing) surpassed other varieties in the SGS. Nitrogen fertilizer replacement value for growing cv. TGX 1440-1E in NGS prior to rice ranged from 17 to 45 kg N ha−1 depending on the reference rice. Grain yield of NERICA1 following 1-year rotation with soybean cv. TGX 1440-1E or TGX 1019-2EB was 1.5 Mg ha−1 greater than the yield obtained from farmers’ control of 2-year continuous IRAT 136 rice cropping. Results indicate that integrating appropriate dual-purpose soybean in an ISFM package can enhance rice productivity in resource-limited smallholder production systems.